Empowering EFL Students with Adaptive Materials: Enhancing Speaking Proficiency and Confidence among Indonesian University Learners - Ramasari, Maria; Ardayati, Ardayati (Universitas Lancang Kuning, 2025)
Spoken English proficiency remains a major challenge for Indonesian university students, often constrained by limited communicative practice, speaking anxiety, and a lack of adaptive learning resources. Existing studies recognize the potential of adaptive learning for improving learner autonomy, yet little research has quantified its effectiveness when embedded in textbook design. This study aimed to develop and evaluate adaptive learning materials to strengthen both spoken English perform76ance and self-confidence among EFL students in Indonesian higher education. Using a Research and Development design with the ADDIE model as adapted by Dick and Carey, the study progressed through systematic phases of needs analysis, design, development, implementation, and evaluation. Data were gathered through expert validation, student and lecturer questionnaires, and pre–post performance tests across one-to-one, small group, and large group trials. Quantitative results revealed strong validation scores from experts (87.50% for content and 88.63% for media), high practicality ratings from lecturers (87.50%) and students (86.44%), and significant gains in speaking performance and confidence after implementation. The developed textbook integrated adaptive, student-centered tasks and interactive feedback mechanisms that fostered measurable improvements in both linguistic competence and affective readiness. These findings confirm the viability of adaptive learning-based materials in bridging gaps of traditional instruction. Beyond the Indonesian context, the study demonstrates how culturally responsive adaptive resources can inform EFL pedagogy more broadly, offering scalable strategies for universities seeking to enhance communication skills and learner confidence in global academic and professional arenas.